Information video segmentation on television: the profesional practice to the automatic indentification - Caldera-Serrano, Jorge; Caro-Castro, Carmen (Cuadernos de Documentación Multimedia, 2018)
It analyzes the different ways in which documentary video segmentation performed in order to identify the minimal discourse unit of analysis in documentation departments of television channels. In parallel, and in response to the digital paradigm shift in television production, analyzes the main formulas developed automatic video segmentation through artificial intelligence. Having determined both realities are trying to implement the best method of segmentation between human and machine, to have its usefulness in information system television documentary. This will provide the main lines of work in semantic video segmentation.